Identification of the product of Toxoflavin lyase: degradation via a Baeyer-Villiger oxidation - Philmus, Benjamin (2012)
Toxoflavin (an azapteridine) is degraded to a single product by toxoflavin lyase (TflA) in a reaction dependent on reductant, Mn(II), and oxygen. The isolated product was fully characterized by NMR and MS and was identified as a triazine in which the pyrimidine ring was oxidatively degraded. A mechanism for toxoflavin degradation based on the identification of the enzymatic product and the recently determined crystal structure of toxoflavin lyase is proposed.